Retrospective audit of antibiotic use in a university general pediatrics department using hospital pharmacy dispensing data - Egle, Leonie (German Medical Science GMS Publishing House, 2021)
Antibiotics are among the most frequently prescribed drugs in children’s hospitals, which is why regular monitoring of antibiotic use in hospitals is of great importance. This retrospective audit (60 months, January 2014 – December 2018) analyzes the antibiotic consumption at a university inpatient department of general pediatrics including neonatal and pediatric intensive care based on pharmacy dispensing data in units of grams per 100 patient days and in Defined Daily Doses per 100 patient days.The results provide potential targets for Antibiotic Stewardship interventions. Conversely, this audit elicits methodological limitations of the method of antibiotic surveillance in pediatrics recommended by the Robert Koch Institute, Berlin.